Specificity of English Mass-Media Discourse - Aminboeva Shakhriniso (Scholars Digest Publishing, 2023)
The article is devoted to the analysis of the specific features of English mass-media discourse. It reveals psychological and sociocultural factors, as well as linguistic peculiarities affecting the specificity of English mass-media discourse. The article concludes that specificity of the discourse of English-language media allows the media to convey complex information clearly and accurately, and also contributes to the reliability and authority of the information transmitted. However, it is crucial to strike a balance between specificity and accessibility so that all viewers can interact with and understand the information being conveyed.
Keywords: specificity, mass-media discourse, accessibility, credibility, familiarity.